Тhe dynamics of the idea of statehood in the context of modern cultural transformations - Semernik, Snezhana Z. (Journal of the Belarusian State University. Sociology, 2023)
The article examines the changes in modern culture that affect the development of the idea of statehood. In particular, the thesis is substantiated that the transformations of the value-semantic sphere of modern society, the dynamics of behavioural stereotypes and life priorities of subjects of social interaction most significantly affect the social structure. The vector of modern cultural transformations is directed towards post-traditionalism, due to which the number of changes in society is increasing, changing not just the forms or ways of representing cultural meanings, but significantly modifying the essence of cultural norms as such. The article substantiates the idea that in a traditional society the idea of statehood (and its concrete embodiment in various state forms) was complementary to the economic and cultural way of society. The formation of the specifics of the state structure in the society of the modern era was most significantly influenced by economic and political determinants. However, the position of economic determinism, which was an avant-garde idea of the modern era and determined the specifics of social development over the past few hundred years in European and many non-European countries, has now reached its inner limit, indicating the limits of the applicability of this idea in the space of modern society. It is noted that the influence of the economy, which is acquiring a global, supranational character, has only intensified in recent decades, generating political and socio-cultural imperatives that initiate risky strategies for social development. In this situation, there is a need to rethink the idea of statehood. The substantial content and political and legal formalisation of this idea can significantly change the architectonics of world society, affect the conditions of existence of most countries and peoples in the modern world. Since economic determinism has exhausted its methodological potential in explaining the most important laws of the development of the idea of statehood, there is a need to supplement the provisions of economic determinism with presumptions of a socio-cultural approach. Verification of the content of cultural transformations affecting the value-semantic sphere of society is a necessary condition for constructing explanatory models of the dynamics of the idea of statehood and the development of the state as such. Apart from the analysis of cardinal changes affecting the foundations of modern culture, it is impossible to form an objective idea of the prospects of the idea of statehood in the near and distant future.